Analysis of Kogabwilhan II Readiness in Conducting Military Operations and Military Operations other than War, OMP and OMSP - Deksino, George (Advances in Social Sciences Research Journal, 2020)
Recently, the development of a strategic environment that changes rapidly and dynamically has a potential threat to the sovereignty of the Unitary State of the Republic of Indonesia (NKRI). To respond to all potential threats and disturbances which could arise, the Indonesian National Army (TNI) carried out a significant organizational transformation by forming new organizational units. Among others are done by forming a joint force of the TNI, namely the Joint Regional Defense Command (Kogabwilhan), which was formed by Presidential Decree Number 27 of 2019 and Regulation of the TNI Commander Number 30 of 2020 as an organization having an important and strategic role in carrying out Military Operations (OMP) and Military Operations Other Than War (OMSP) synchronously. How is the readiness of Kogabwilhan II in organizing OMP and OMSP? This becomes the research question aiming to analyze the readiness of the units in the area of responsibility of Kogabwilhan II such as; Kodam XIII/Merdeka, Kodam V/Brawijaya, Korem 131/Santiago, Koarmada II/Surabaya, Lantamal VIII Manado, Sam Ratulangi Air Base, Lanud Muljono Surabaya and Iswahyudi Magetan Air Base. With a descriptive qualitative research approach using Spradley analysis techniques including place studies, actor studies and activity studies, it was found that human resources (personnel), defense equipment (logistics), software and budget aspects were still limited.